Self-report sports injury mobile application with Chatbot / Mohamad Hakimi Mohamad Noor - Mohamad Noor, Mohamad Hakimi (2021)
Students from Faculty Sport Science and Recreation having difficulty to finish their assessment due to Covid-19. All classes are conduct online. Hence, they cannot diagnose injured athletes or person face-to-face. This project aims to develop Self-Report Sports Injury Mobile Application with Chatbot (SRSIMAC) for Faculty Sport Science and Recreation students as part of their learning and training using the SOAP notes method. Musculoskeletal Disorder (MSD) is degenerative diseases and inflammatory conditions that cause pain and impair normal activities. It affects many different parts of the body include Upper Limb Disorders (ULD), Lower Limb Disorders (LLD), and also back (upper and lower). MSD involves soft tissue. Sometimes, there are no visible signs of injury. These assessments are about self-reported or evaluation process. The developer implements a modified waterfall and uses four phases out of seven during develops the project. It includes requirement gathering and analysis, design, implementation, and testing. The developer uses an online questionnaire and interview method to collect information. Then, rule the question for the third party chatbot using kommunicate_flutter packages in the mobile application. After finish developing the project, stakeholder will test the mobile apps based on the test cases. Once the test pass, SRSIMAC is ready to use by Faculty Sport Science and Recreation students and lecturers to diagnose and plan rehabilitation treatment for injured athletes or persons.